Sediment and phosphorus transport during flood events in a Mediterranean temporary river - Garnier, Monica; Pappagallo, Giuseppe; Holman, Ian P. (Springer, 2024)
Flood events, whose number and intensity are predicted to increase in the Mediterranean region, are difficult to monitor. This causes the number of observations of suspended sediment and total phosphorus concentration (|SS| and |TP|, respectively) during their occurrence to be still scarce. Non-perennial or temporary water bodies, which react more promptly to rainfall events, represent ideal natural observatories. In this study, observations of streamflow, |SS| and |TP|, carried out during some flood events, in the Celone river basin, a temporary river located in south-eastern Italy, are presented. The research examined the correlations between flows, concentrations and loads of sediment and phosphorus and investigated factors that influence sediment and phosphorous dynamics in the river basin. The results show no relationship between the time of the year and the precipitation quantity of each event. The high coefficient of determination of the |SS|–|TP| correlations (R2 = 0.67 on average) proves the importance of soil erosive processes in the delivery of phosphorus to the river. More than 73% of the total suspended sediment load and 83% of total phosphorus load in the period 2010–2011 were transported during the 11 monitored events. In addition to the discharge, |SS| and |TP| also depend on numerous other factors related to land management, such as soil cover and fertilizations. The study, thanks to the improved understanding of the mechanisms governing sediment and phosphorus losses, represents a useful contribution for river basin authorities who have to draw up management plans aimed at preventing eutrophication phenomena and soil fertility reduction.
Keywords: Flood event; Suspended sediment; Total phosphorus; Soil erosion; Temporary river; Runoff